Altered gut ecosystems plus the microbiota’s potential for rapid evolution: A recipe for inevitable change with unknown consequences - Celina You (Elsevier, 2021)
In a single human gut, which is estimated to produce 1000-times more bacteria in a single day than the entire human population on Earth as of 2020, the potential for evolution is vast. In addition to the sheer volume of reproductive events, prokaryotes can transfer most genes horizontally, greatly accelerating their potential to evolve. In the face of this evolutionary potential, Westernization has led to profound changes in the ecosystem of the gut, including increased chronic inflammation in many individuals and dramatically reduced fiber consumption and decreased seasonal variation in the diet of most individuals. Experimental work using a variety of model systems has shown that bacteria will evolve within days to weeks when faced with substantial environmental changes. However, studies evaluating the effects of inflammation of the gut on the microbiota are still in their infancy and generally confounded by the effects of the microbiota on the immune system. At the same time, experimental data indicate that complete loss of fiber from the diet constitutes an extinction-level event for the gut microbiota. However, these studies evaluating diet may not apply to Westernized humans who typically have reduced but not absent levels of fiber in their diet. Thus, while it is expected that the microbiota will evolve rapidly in the face of Westernization, experimental studies that address the magnitude of that evolution are generally lacking, and it remains unknown to what extent this evolutionary process affects disease and the ability to treat the disease state.